2007
DOI: 10.1007/s11027-007-9127-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of winter temperature and climate change on the survival and future range expansion of the hemlock woolly adelgid (Adelges tsugae) in eastern North America

Abstract: Adelges tsugae , Climate change, Hemlock, Invasive species, Woolly adelgid,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
130
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 30 publications
2
130
0
Order By: Relevance
“…As such, patterns of distribution in insects are often related to latitude, altitude, and local topography (Hoffmann 2010). For newly introduced species, local temperatures and overwintering conditions can determine a species' ability to establish and become invasive (Bale 2002, Paradis et al 2008. Temperature can also determine if an established insect becomes a pest, and outbreaks of insect pests have been related to changing temperature conditions (Bale et al 2002) and overwintering success (Virtanen et al 1996, Roland et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As such, patterns of distribution in insects are often related to latitude, altitude, and local topography (Hoffmann 2010). For newly introduced species, local temperatures and overwintering conditions can determine a species' ability to establish and become invasive (Bale 2002, Paradis et al 2008. Temperature can also determine if an established insect becomes a pest, and outbreaks of insect pests have been related to changing temperature conditions (Bale et al 2002) and overwintering success (Virtanen et al 1996, Roland et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(a) (b) Figure 6. Expected (a) extreme minimum winter temperatures, (b) winter mortality of hemlock woolly adelgid sistens predicted by Equation (2), and (c) population growth rates (r = P/S) from sistens (S) to progrediens (P) using Equation ( Paradis et al [37] estimated that mortality of 91% or less would result in the expansion of HWAs. Our estimates of where the 91% mortality isobar is for the current 30-year normals fit closely with the current distribution of HWAs, although in Vermont and New Hampshire, HWA has expanded north of the 91% mortality isobar (Figures 1 and 7a).…”
Section: Climate Change Projectionsmentioning
confidence: 99%
“…Eastern hemlocks prefer moist to very moist soils but can also tolerate drier soils and ridgetops [4]. Hemlocks Paradis et al [37] reported that when the mean winter temperature is equal to or above −5 • C, HWA mortality was below 91% and under these conditions, HWA will disperse to new areas. Based on a 15-year study of winter mortality of HWA in Connecticut, Cheah [38] reported that the absolute minimum temperature was the best predictor of mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If u(t 0 , x) is assumed to be the initial value for the model (58), then the solution u(t, x) satisfies the integral equation (79). Since when t > t 0 , x satisfies…”
mentioning
confidence: 99%